Factors Supporting the Academic Success of Students with Disabilities in Inclusive Universities - Dewi, Eva Puspita; Razak, Ahmad; Tetteng, Basti; Asmiati, Asmiati; Amalia, Riza (Indonesian Journal of Disability Studies, 2025)
There are many factors that influence the learning process of students with disabilities in higher education. This study aims to determine the factors that support the academic success of students with disabilities in inclusive universities. Researchers in this study used a qualitative approach. Data collection in this study was conducted using questionnaires and interviews. This study involved thirty-seven students with disabilities, consisting of students with visual disabilities, physical disabilities, mental disabilities, and Deaf students. They are students with disabilities who excel in academic and non-academic fields. Their success is achieved with hard work and help or support from others. The results of this study found that there are two factors that support the academic achievement of students with disabilities in inclusive universities, namely internal factors and external factors. Internal factors are factors that come from within students with disabilities, such as motivation, self-confidence, locus of control, mental strength, adaptability, intellectual ability, and communication skills. External factors are factors that come from outside students with disabilities, namely support from others, facilities and infrastructure, and learning tools.